PENGARUH PENGETAHUAN TENTANG POLA MAKAN IBU HAMIL TERHADAP KEJADIAN BBLR - Eko Sri Wulaningtyas; Entin Srihadi Yanti; Ardina Rezky Noeraini; Oktavia Puspitasari (Universitas Pesantren Tinggi Darul Ulum, 2022)
During pregnancy, a lot of preparation is needed, one of which is the diet during pregnancy. Mother's knowledge about good nutrition is expected that the nutritional status of the mother and her baby is also good, with good knowledge of the mother, pregnant women will be able to adjust their food patterns so that the baby can be born normally. This study was to determine the effect of knowledge about the diet of pregnant women on the incidence of LBW in the Working Area of ??the Islamic Boarding School Health Center, Kediri City. The research design used in this study is Prospective Analytic. The population of this study were 30 pregnant women using purposive sampling. Data collection technique with a questionnaire and is the primary data. The collected data was edited, coding, scored and tabulated and then the spearman rank correlation was calculated. From the results of this study, it was found that most of the respondents had less knowledge about diet during pregnancy, namely 14 respondents (46.7%) out of 30 respondents, 16 LBW babies (53.3%) were born from 30 babies born to respondents. This study was supported by statistical tests in which P = 0.039 <0.05 so that Ho was rejected with a correlation rate of 0.600, this means that there is a strong positive influence between knowledge of pregnant women's diet on the incidence of LBW. This is because the mother's lack of knowledge causes the mother's diet to be incorrect so that the baby born will have low birth weight. There is a significant effect of knowledge about diet during pregnancy on the incidence of LBW. Keywords: Mother's knowledge, Diet during pregnancy, Low birth weight babies